OPINIONS ON THE USE OF ELECTRONIC DOCUMENT SYSTEM BY PERSONNEL AT THE GOVERNMENT PUBLIC RELATIONS DEPARTMENT - Inmee, Naviya; Chairatana, Pirada (Journal of MCU Nakhondhat, 2024)
The objectives of this study are 1) To Study the opinions of the Government Public Relations Department (PRD) personnel on the use of electronic document system and 2) To Compare the use of electronic document system by the PRD personnel classified according to their personal factors. The study provides information on the use of electronic document system by the PRD personnel in three aspects: 1) Efficiency of the electronic document system (convenient, fast, and safe), 2) Information technology accommodating the use of the electronic document system (availability of IT equipment), and 3) Staff responsible for handling the electronic document system. The sampling group in the study consisted of 350 PRD personnel using the PRD electronic document system and operating in both central and regional offices during November - December 2023. The distribution of questionnaires was applied as a tool to gather information. The collected data were analyzed with the use of a statistical package. The statistics used were percentage, average, standard deviation, the t - test Independent Samples, and One - Way ANOVA. The statistical significance was set at the 0.05 level. The results of this study show that the use of electronic document system by the PRD personnel was at a high level. The average score was 4.37 in the efficiency of electronic document systems (convenient, fast, and safe). Regarding information technology accommodating the use of the electronic document system (availability of IT equipment), the average score was 4.03. As for staff responsible for handling the electronic document system, the average score came to 3.67. The hypothesis testing indicates that the use of electronic document system by the PRD personnel did not differ, despite their differences in genders, ages, educational backgrounds, occupations and working periods.